Introducing Christian Spirituality to Joseon KoreaThree Responses from Confucian Scholars - Chung, So-Yi (Religions, 2018)
When the books written by Jesuit missionaries were introduced to Joseon Korea via China during the 18th century, Joseon Confucian scholars were drawn to not only western science and technologies but also to theological ideas centered on Christian spirituality. Among many foreign conceptions, the most alien were the following three: immortality of the soul; eternal life in heaven or in hell after death; and finally, the resurrection of the body. There had been three responses from all levels of society: refutation, recognition, and reconciliation. First, Shin Hudam (1702-1761) wrote a book, Disputation on Western Learning, to dispute the above three doctrines as being most unreasonable and contradictory. Meanwhile, Jeong Yag-Jong (1760-1801) found that the doctrines were the true path to the salvation of human suffering and wrote the first catechistic book in vernacular Korean in the way that appealed to common people with Confucian backgrounds. Finally, Jeong Yag-Yong (1762-1836) was extremely careful, neither embracing nor rejecting, yet suggested alternative ways to address the core Christian theological problems without crossing the boundaries of Confucianism. All three were active dedicated responses to Christian spirituality and genuine Christian-Confucian dialogues, which also reflected common concerns and attitudes toward a new religion in Korean society.